Durvalumab in urothelial cancers. Issue 4 (3rd April 2018) - Lavaud, Pernelle; Hamilou, Zineb; Loriot, Yohann; Massard, Christophe
ABSTRACT: Introduction : Urothelial bladder cancer is one of the most predominant malignancies worldwide with a poor prognosis when presented at an advanced or metastatic stage. Improving the therapeutic landscape in this setting has been an unmet medical need. Palliative cisplatin-based chemotherapy is currently the standard of care in first line therapies, but many patients are ineligible and few alternative therapies exist. Moreover second-line chemotherapy has minimal activity. Recently, immune-checkpoint inhibitors have shifted the therapeutic armamentarium of bladder cancer and it is now necessary to redesign the therapeutic paradigm. Areas covered : In this article, we focus on the development of durvalumab and provide an overview of the safety, activity, efficacy and future perspectives of this drug in urothelial carcinoma. Expert commentary : Durvalumab is a well-tolerated drug and demonstrated major and durable response in advanced bladder cancer. Combinations with durvalumab will probably emerge as promising therapeutic strategies for the treatment of urothelial carcinoma. Further research efforts are needed to identify predictive biomarkers of response to immune-oncology agents.